The Organic Degradation and Potential Microbial Function in a 15-Day Sewage Sludge Biodrying. Issue 1 (2nd January 2020) - Wang, Yang-Yan; Zheng, Sheng-Wei; Gao, Ding; Cai, Lu
Abstract: To meet the challenge of increased sludge generation, shortening of biodrying periods are required. This study assesses a shortened sewage sludge biodrying period of 15 days. The fundamental physicochemical properties of samples from different phases were determined, the functional groups were identified using infrared spectroscopy and the biodrying associated microbial functions were annotated against gene databases. After a 15-day biodrying period, the moisture content, readily degradable carbohydrate, lignocellulose and protein levels were significantly reduced. The distinct attenuation of peaks identified by infrared spectroscopy, indicates that the degradation of most lipids, proteins and polysaccharides in the biodrying matrix had reached equilibration on Day 15 and following this biosynthesis may result in an increased polysaccharide content. However, the biodrying matrix on Day 20 was only partially matured. Firmicutes, Actinobacteria and Proteobacteria were the most ecologically dominant phyla. These ecologically dominant microorganisms were also functionally dominant in biodrying associated metabolic pathways (glycolysis, amino sugar and nucleotide sugar metabolism, starch and sucrose metabolism), as well as containing carbohydrate-active enzyme families. The modified 15-day biodrying period reduced the treatment time and achieved a competent biodrying result without increasing the operating costs. The 15-day treatment would increase the rate of existing systems or decrease the capital cost of new systems.